Reliability performance evaluation and integration of routing algorithm in shuffle exchange with minus one stage - Md Yunus, Nur Arzilawati (2012)
Multistage interconnection networks offer an economical solution to communication and interconnection between system components. Optical Multistage Interconnection Networks (OMINs) are designed to provide an effective communication in switching. OMINs consist of stages that can route the switching through the path. OMINs with the Omega property considered as a practical connection to connect a large number of processors to establish multiprocessor system. In this types of network the major problem occur when the switches failed to route in the stage, if these situations occur the switching need to route to an alternative path to avoid from system failure. Shuffle Exchange Networks (SENs) have been widely considered as practical interconnection systems due to their size of it switching elements (SEs) and uncomplicated configuration. It can helps in fault tolerance and reduce the latency. This research emphasize on the SENs architecture to derived estimation point of reliability value specifically for reliability performance in the interconnection networks. The proposed Shuffle Exchange Network with Minus One Stage (SEN-) is design to increase the reliability performance in the interconnection networks. The SEN- is compared among others three SEN architecture known as Shuffle Exchange Network (SEN), Shuffle Exchange Network with Additional Stage (SEN+), and Shuffle Exchange Network with Two Additional Stages (SEN+2) to determine the highest reliability performance in SEN. There are three parameters used to measure the reliability performance on these four types of SENs namely terminal reliability, broadcast reliability and network reliability. In addition this thesis also incorporates integration of routing algorithm to the SENs architecture. Several routing algorithm derived by past researches are also implemented for comparison purposed. These routing algorithms are Zero X, Zero Y, ZeroYbit, ZeroXbit, Sequential Increasing and Sequential Decreasing Algorithm. These six algorithms are integrated with four different types of SENs, and all the algorithms are analyze in this research. The results of this study show that the proposed SEN- increase the reliability performance approximately 39% as compared to other SENs architecture. The performance analysis showed that the integration of Sequential algorithm in SEN- architecture yield the better results in term of average number of passes and integration of ZeroX algorithm with SEN- yield a better results in term of execution time. For the conclusion it is prove in this research the proposed SEN- much more reliable than other SENs architecture. The SEN- gain the reliability performance in the interconnection network and also by integrate the SEN- in the routing algorithm it achieve the best performance among all the algorithms being tested in this research.